Chediak-Higashi syndrome: A review of the past, present, and future. (2020) - Sharma, Prashant; Nicoli, Elena-Raluca; Serra-Vinardell, Jenny; Morimoto, Marie; Toro, Camilo; Malicdan, May Christine V.; Introne, Wendy J.
Graphical abstract: Abstract : Since the initial description of Chediak-Higashi syndrome (CHS), over 75 years ago, several studies have been conducted to underscore the role of the lysosomal trafficking regulator ( LYST ) gene in the pathogenesis of disease. CHS is a rare autosomal recessive disorder, which is caused by biallelic mutations in the highly conserved LYST gene. The disease is characterized by partial oculocutaneous albinism, prolonged bleeding, immune and neurologic dysfunction, and risk for the development of hemophagocytic lympohistiocytosis (HLH). The presence of giant secretory granules in leukocytes is the classical diagnostic feature, which distinguishes CHS from closely related Griscelli and Hermansky-Pudlak syndromes. While the exact mechanism of the formation of the giant granules in CHS patients is not understood, dysregulation of LYST function in regulating lysosomal biogenesis has been proposed to play a role. In this review, we discuss the clinical characteristics of the disease and highlight the functional consequences of enlarged lysosomes and lysosome-related organelles (LROs) in CHS.